PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN UD.PUTRA UYUNG JAYA - Indra Putra , Anak Agung Ngurah Manik; Sumaji, Yoseva Maria Pujirahayu (Universitas Ciputra Surabaya, 2023)
This research aims to determine the partial and simultaneous effects of work motivation and work environment on employee job satisfaction. The population in this study consisted of 40 respondents. The data analysis techniques used in this study were Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination Test, F-Test, and t-Test. The results of the study showed that work motivation had a significant positive effect on employee job satisfaction, work environment had a significant positive effect on employee job satisfaction, and simultaneously, work motivation and work environment had a significant effect on employee job satisfaction. The magnitude of the influence of the independent variables on employee job satisfaction was 85.7%. The researchers suggest that the superiors at UD. Putra Uyung Jaya provide motivation that can be beneficial for their employees and create a comfortable work environment for their subordinates, such as providing suitable rooms and ensuring good air circulation and minimal noise.